Exosomal RNAs in diagnosis and therapies - Pranay Narang; Morish Shah; Vladimir Beljanski (Non-coding RNA Research, 2022)
The field of extracellular vesicles has been rapidly developing after it became evident that a defined subset of vesicles, called exosomes, can modulate several biological functions in distant cells and tissues. Exosomes range in a size from 40 to 160 nm in diameter, are released by majority of cells in our body, and carry molecules which reflect the cell of origin. The types of biomolecules packed, their respective purpose, and their impact on the physiological state of distinct cells and tissues should be understood to advance the using of exosomes as biomarkers of health and disease. Many of such physiological effects can be linked to exosomal RNA molecules which include both coding and non-coding RNAs. The biological role(s) of various exosomal RNAs have started being recognized after RNA sequencing methods became widely available which led to discovery of a variety of RNA molecules in exosomes and their roles in regulating of many biological processes are beginning to be unraveled. In present review, we outline and discuss recent progress in the elucidation of the various biological processes driven by exosomal RNA and their relevance for several major conditions including disorders of central nervous system, cardiovascular system, metabolism, cancer, and immune system. Furthermore, we also discuss potential use of exosomes as valuable therapeutics for tissue regeneration and for conditions resulting from excessive inflammation. While exosome research is still in its infancy, in-depth understanding of exosome formation, their biological effects, and specific cell-targeting will uncover how they can be used as disease biomarkers and therapeutics.